The host tRNA epitranscriptome: A new player in RNA virus infections - Talló-Parra, Marc; Muscolino, Elena; Díez, Juana (Frontiers in Virology, 2022)
Viruses completely depend on the host translation machineries to express the viral proteins. Recent data reveal an unprecedented interaction of a positive strand RNA ((+)RNA) virus with the host tRNA epitranscriptome to favor viral protein expression via a specific reprogramming of codon optimality that ultimately favors decoding of the viral codons. We propose that this feature is shared by multiple (+)RNA viruses and that the involved tRNA modifying enzymes represent promising novel targets for the development of broad-spectrum antivirals.